Proceedings of the International Workshop on Rock Mass Classification in Underground Mining - Mark, Christopher; Pakalnis, Rimas Thomas, 1956-; Tuchman, Robert J. (Information circular (National Institute for Occupational Safety and Health) ;, 2007)
"Rock mass classification is widely used throughout the underground mining industry--in both coal and hardrock mines. It is used in all stages of the mining process, from site characterization to production operations. The goal of the International Workshop on Rock Mass Classification in Underground Mining was to provide a forum for leading practitioners of rock mass classification to come together and share their methods and experiences with the technique. The workshop was held in Vancouver, British Columbia, Canada, on May 31, 2007"--Page 1